SISTEM INFORMASI PINJAMAN DANA DAN PEMBELIAN BARANG PADA KOPERASI SECARA KREDIT BERBASIS WEB - Adi Supriyatna (LPPM Universitas Bina Sarana Informatika, 2014)
Cooperative is business entity which consists of persons or bodies on cooperation with based upon that its activities as motion public economy can be realized on the principle of family. Koperasi is cooperative focus its business activities in the field of business loan and save. Currently the growth of business activities cooperative more rapidly and in line with the needs of members of a cooperative economic activities. To meet the need then koperasi expand business activities by opening new business unit waserba, namely where that it provide various kinds of goods ranging from consumer electronics until motorcycle with credit payments system. It is hoped the information system to simplify the administrative process business activities of existing in the koperasi particularly concerning credit sector goods by members of a cooperative as well as to improve the service to the members of a cooperative as access to information quickly and accurately. The aim of this research is to produce a dynamic web site that can be presenting information business activities of existing in the koperasi and can be used as as a means of communication between manager with members of a cooperative so as to maximize service to members without limited by time and distance and ease in the preparation of the report, the manufacture and so precise information faster obtained to support decision-making process. Keywords: Information System, Web Base, Cooperative, Credit.